Funding the Cause: How Public Interest Law Organizations Fund Their Activities and Why It Matters for Social Change. Issue 1 (28th February 2013) - Albiston, Catherine R.; Nielsen, Laura Beth
<x xml:space="preserve">Abstract</x> Most of the work of public interest law organizations does not make money. How do these organizations survive, given the economic realities of law practice? Drawing on survey data from a national random sample of public interest law firms, we investigate how funding models vary across public interest organizations and how funding sources affect these organizations' activities. We find funding structures have, over time, shifted away from foundation support toward government grants. Compared to other organizations, however, conservative organizations draw significantly less of their budget from federal and state grants, and significantly more of their budget from private contributions. Conservative organizations are significantly less likely than other organizations to rely on funding that prohibits engaging in class actions, receiving attorney's fees, or lobbying. Respondents reported that funding restrictions hamper their ability to negotiate favorable settlements, bring about systemic change, and represent vulnerable client communities. We close with a comparative institutional analysis of different funding models.